How Should Imaging Direct/Orient Management of Rectal Cancer? - Bhoday, Jemma; Balyasnikova, Svetlana; Wale, Anita; Brown, Gina (Clinics in Colon and Rectal Surgery, 2017)
Modern rectal cancer management is dependent on preoperative staging, and radiological assessment is a crucial part of this process. Imaging must provide sufficient information to guide preoperative decision-making that is reliable and reproducible. Different methods have been used for local staging; however, magnetic resonance imaging (MRI) has shown to be the most reliable tool for this purpose. MRI offers prognostic information about the patients and guides the decision between neoadjuvant treatment and total mesorectal excision alone. Also, not only the initial staging but also restaging by MRI can provide significant information regarding tumor response that is essential when considering alternative approaches.
Keywords: rectal cancer; magnetic resonance imaging; local staging